Real-time tracking of mRNP complex assembly reveals various mechanisms that synergistically enhance translation repression - Payr, Marco; Meyer, Julia; Geissen, Eva-Maria; Hennig, Janosch; Duss, Olivier (Cell reports, 2025)
Protein biosynthesis must be highly regulated to ensure proper spatiotemporal gene expression and thus cellular viability. Translation is often modulated at the initiation stage by RNA-binding proteins through either promotion or repression of ribosome recruitment to the mRNA. However, it largely remains unknown how the kinetics of mRNA ribonucleoprotein (mRNP) assembly on untranslated regions (UTRs) relate to its translation regulation activity. Using Sex-lethal (Sxl)-mediated translation repression of msl-2 in female fly dosage compensation as a model system, we show that different mechanisms in mRNP assembly synergistically achieve tight translation repression. Using multicolor single-molecule fluorescence microscopy, we show that Sxl targets its binding sites via facilitated diffusion and multivalent binding, Unr recruitment is accelerated over 500-fold by RNA-bound Sxl, and Hrp48 further stabilizes RNA-bound Sxl indirectly via ATP-independent RNA remodeling. Overall, we provide a framework to study how multiple RBPs dynamically cooperate with RNA to achieve function.